2020
DOI: 10.1016/j.heliyon.2020.e04580
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the mercury concentration in the hair of young residents of the Vologda region, Russia

Abstract: The main aim of this study was to assess the level of mercury accumulation in the hair of students studying in the Vologda Region, Russia. Particular attention is devoted to clarifying the relationship between the metal concentration in the hair and the amount of fish in the diet. It was found that the mercury content in the hair of Vologda Region residents aged 17–21 is in the range from less than 0.002 mg/kg to 1.69 mg/kg, the median of the indicator for the entire sample is 0.14 mg/kg. The median value of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…There was no significant difference between males and females of Aby respondents contrary to Frambo participants However, considering the whole sample, the difference associated with gender persists. Our finding concerning the lowest mercury level in women was in accordance to others results such us those of [51] and [52], contradictory trend was observed by [50] and [53].…”
Section: Mercury Concentration In Hair By Living Residence According ...supporting
confidence: 91%
See 1 more Smart Citation
“…There was no significant difference between males and females of Aby respondents contrary to Frambo participants However, considering the whole sample, the difference associated with gender persists. Our finding concerning the lowest mercury level in women was in accordance to others results such us those of [51] and [52], contradictory trend was observed by [50] and [53].…”
Section: Mercury Concentration In Hair By Living Residence According ...supporting
confidence: 91%
“…At the same time, we noticed a significant highest Hg level in Aby village, this difference of mercury level may due to frequency [50], high rate of fish consumption in their dietary habits and its species composition like many favored predatory fish [51].…”
Section: Mercury Concentration In Hairmentioning
confidence: 67%
“…Our results were in line with other authors who have shown that the place of residence has the most significant influence on the results (38,(72)(73)(74)(75) . In many residences, consumption of fish, whose meat is contaminated with Hg, has the highest importance (76,77) , but fish in the Malagasy's diet are rare. However, it must be remembered, that girls from these two studied places of residence consumed different food.…”
Section: Toxic Elements Accumulation In Relation To Nutritional Statu...mentioning
confidence: 99%